ACCURACY OF AC AND AT METHODS IN MILK RECORDING IN THE BALKAN GOATS BREED IN MACEDONIA - NIKOLA PACINOVSKI1; VLADIMIR DZABIRSKI2; GEORGE DIMOV3; KOCO PORCU2; GOCE CILEV4; ELENA EFTIMOVA1; NEDELJKA NIKOLOVA1; NATASA MATEVA1; BONE PALASEVSKI1; GORAN TRAJKOVSKI2; ANA PALASEVSKA1 (Bulgarian Journal of Agricultural Science, 2018)
The aim of this research was to compare the AC and AT methods (as alternative methods) with A4 method (as referent method), for determination of milk production, on the day of recording of the indigenous Balkan goat, in the period of 2014-2016 with milking of goats in the morning and evening. Simultaneously, the influence of the following factors has been tested: year (year of kidding), lactation, month of kidding, milk yield level. It was determined that the largest deviation in the prediction of milk yield according to the AT method during morning milking was determined in 2016 with milk yield underestimated for -5.3 L, whereas the smallest deviation was registered in 2015 with milk yield underestimated for -1.8 L. The largest deviation in the prediction of milk yield according to the AC method during morning milking was determined in goats in first lactation, with milk yield overestimated for +3.8 L, whereas the smallest deviation was determined in goats in fourth lactation with milk yield underestimated for -0.3 L. With the analysis of all abovementioned factors, it was determined that the AT method is more suitable as alternative and cheaper method for determination of accurate amount of milk.
Keywords: Balkan goat, daily lactation, method AT, method AC, predicted daily milk yield